ANALISIS TEGANGAN STATIK STANDAR SAMPING SEPEDA MOTOR MATIC MENGGUNAKAN BAHAN STEEL ALLOY DENGAN SOFTWARE SOLIDWORK - Ratna Fajarwati Meditama; Diama Rizky Septiawan; Agus Dwi Putra; Bisyri Nur Wahid (Universitas Islam Malang, 2024)
This study presents a static stress analysis on the side stand of a matic motorcycle using Steel Alloy material, applying the finite element method and SolidWorks software. Motorcycles are a popular means of transportation, especially in rural areas where users often modify the side stand to support additional loads. The side stand is a critical component that allows the motorcycle to remain stable when parked. However, this component frequently encounters damage due to loads exceeding its initial design capacity. This research aims to evaluate the structural strength and safety factor of the side stand under a 2240 N load. Simulation results indicate that the maximum stress experienced remains below the yield strength of the Steel Alloy used. The obtained safety factor supports the material's application in side stand structures, provided that load limits are observed. This study is expected to contribute to the development of more load-resistant side stand designs, especially for rural usage needs.